2015
DOI: 10.4054/demres.2015.33.26
|View full text |Cite
|
Sign up to set email alerts
|

Educational differences in timing and quantum of childbearing in Britain

Abstract: BACKGROUNDIncreased postponement of fertility, especially among higher-educated women, means it is important to know whether women recuperate births at older ages, but evidence for the UK is lacking. The extent to which the timing and quantum of mothers' fertility underlie the strong educational gradient in completed family size is also unclear. OBJECTIVEWe investigate the relative contributions of childlessness, timing, and quantum to educational differences in completed fertility within cohorts born between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(82 citation statements)
references
References 59 publications
(75 reference statements)
2
71
0
2
Order By: Relevance
“…In England and Wales and the United States these relatively high fertility levels partly arise from social polarisation in fertility (Ekkert-Jaffé et al 2002;Sardon 2006aSardon , 2006b): relatively high childlessness among women with a university degree contrasts with a high share of large families among the lower-educated (Berrington, Stone, and Beaujouan 2015;Schoen 2006). This pattern is partly driven by unplanned pregnancies, which are most common among lower-educated women (Musick et al 2009).…”
Section: Discussion: the Regional Context Of Cohort Fertility Declinesmentioning
confidence: 99%
“…In England and Wales and the United States these relatively high fertility levels partly arise from social polarisation in fertility (Ekkert-Jaffé et al 2002;Sardon 2006aSardon , 2006b): relatively high childlessness among women with a university degree contrasts with a high share of large families among the lower-educated (Berrington, Stone, and Beaujouan 2015;Schoen 2006). This pattern is partly driven by unplanned pregnancies, which are most common among lower-educated women (Musick et al 2009).…”
Section: Discussion: the Regional Context Of Cohort Fertility Declinesmentioning
confidence: 99%
“…Earlier transition into marriage and parenthood is associated with a higher total number of children (Berrington, Stone, & Beaujouan, 2015;Sobotka, 2003), not only because people who are prone to marry early tend to want to have more children, but also because women's fecundity declines with age. Higher education is generally associated with later transition into marriage, especially for women (Becker & Lewis, 1974;Gangadharan & Maitra, 2001).…”
Section: Figure 1: Period Total Fertility Rates 1930-1980mentioning
confidence: 99%
“…It should be noted that cohort changes in the timing of the first birth by education may also help to explain the observed patterns. As previous studies have shown, the rise in the age at first birth across cohorts has been much more pronounced among highly educated women than among their less educated peers (Berrington et al 2015b;Ratcliffe and Smith 2006). Since less educated women tend to have their children relatively early in the life course, they are also less likely than better educated women to be married when they have their first child.…”
Section: Discussionmentioning
confidence: 69%
“…Previous studies have shown the timing of the first birth is becoming increasingly polarised by education across birth cohorts in Britain (Berrington et al 2015b;Ratcliffe and Smith 2006). This trend may be the result of the differential opportunity costs of early childbearing by level of education.…”
Section: Education and Family Formation Patterns In Britainmentioning
confidence: 99%